The Management Gaps toward Inclusive Education Implementation at Higher Education in Indonesia - Fina Riswari; Fiolina Hana Puspitasari; Neny Yuniarti; Silvana Rahma Iswahyudi; Asep Sunandar; Ediyanto Ediyanto; Ahsan Romadlon Junaidi (Indonesian Journal of Disability Studies, 2022)
The commitment to implementing inclusive education in Indonesia is already at the higher education level. However, in reality, disabled people still have difficulty obtaining opportunities to study in university. Concerning the gap in inclusive education (commitment and implementation), this article aims to examine the inclusive education management performance at universities in Indonesia. This review is critical because only 401 disabled people in Indonesia are registered as students at various universities in Indonesia. The articles in the current study go through three stages of narrative review: determining the scope of the research focus, determining the urgency and novelty of the research, and determining the research formulation and objectives. A study of 14 articles through the Google Scholar database was published in 2000-2021. The study results show that most universities in Indonesia are still not open to inclusive education and the admission of students with disabilities implementation. In addition, universities in Indonesia are not ready to provide management and facilities that support the learning process and the accessibility of the campus environment to suit the needs of students with disabilities. Human resources in higher education such as lecturers and education staff are not ready to provide services and modify learning for disabled students.